Assessment of renal function in routine care of people living with HIV on ART in a resource-limited setting in urban Zambia - Deckert, Andreas; Neuhann, Florian; Klose, Christina; Bruckner, Thomas; Beiersmann, Claudia; Brune, Maik; Zeier, Martin (PLOS ONE, 2017)
Introduction Data on renal impairment in sub-Saharan Africa (SSA) remains scarce, determination of renal function is not part of routine assessments. We evaluated renal function and blood pressure in a cohort of people living with HIV (PLWH) on antiretroviral treatment (ART) in the Renal Care Zambia project (ReCaZa). Methods Using routine data from an HIV outpatient clinic from 2011-2013, we retrospectively estimated the glomerular filtration rate (eGFR, CKD-Epi formula) of PLWH on ART in Lusaka, Zambia. Data were included if adults had had at least one serum creatinine recorded and had been on ART for a minimum of three months. We investigated the differences in eGFR between ART subgroups with and without tenofovir disproxil fumarate (TDF), and applied multivariable linear models to associate ART and eGFR, adjusted for eGFR before ART initiation. Results and discussion Among 1118 PLWH (63,3% female, mean age 41.8 years, 83% ever on TDF; median duration 1461 [range 98 to 4342] days) on ART, 28.3% had an eGFR <90 ml/min, and 5.5% <60 ml/min at their last measurement. Information on other conditions associated with renal impairment was not systematically documented. Fourteen per cent of the PLWH who later switched to TDF-free ART had an initial eGFR lower 60ml/min. Nineteen percent had first-time hypertensive readings at their last visit. The multivariable models suggest that physicians acted according to guidelines and replaced TDF-containing ART if patients developed moderate/severe renal impairment. Conclusions Assessment of renal function in SSA remains a challenge. The vast majority of PLWH benefit from long-term ART, including improved renal function. However, approximately 5% of PLWH on ART may have clinically relevant decreased eGFR, and 27% hypertension. While a routine renal assessment might not be feasible, strategies to identify patients at risk are warranted. Targeted monitoring prior and during ART is recommended, however, should not delay ART access.